The availability of drugs for stable COPD treatment in China: a cross-sectional survey - Dongru Du; Xueru Hu; Qiunan Zuo; Dan Xu; Tao Zhu; Tao Fan; Jiao Yang; Weiguo Xu; Hailong Wei; Kangzhuo Baima; Ying Zhang; Yanhui Gu; et al. (npj Primary Care Respiratory Medicine)
Abstract This survey aimed to investigate the availability of drugs for stable chronic obstructive pulmonary disease (COPD) treatment in Chinese hospitals and to determine whether drug availability significantly varied among hospitals with different characteristics. A well-constructed questionnaire was designed according to the Chinese Guidelines for the Diagnosis and Management of COPD (revised version 2021). Both inhaled drugs (monotherapy, double therapy and triple therapy) and oral drugs (expectorants, theophylline, antibiotics, and bacterial lysates) were included in this survey. Doctors from different hospitals completed the survey via WeChat. The availability of each category and kind of drug was analyzed based on final valid responses. Subgroup analyses were also conducted to reveal drug availability in hospitals with different characteristics. A total of 1018 hospitals with different characteristics were enrolled in this survey, with 53.73% of which establishing independent respiratory departments. Insufficient supply of COPD-related drugs was observed, with only short-acting β2 agonists (80.6%), expectorants (88.2%) and antibiotics (84.3%) reaching 80%. Results of subgroup analyses suggested that primary hospitals were associated with poorer availability of all kinds of drugs than secondary and tertiary hospitals (all p < 0.001). Most inhaled drugs did not reach an availability of 20% in primary hospitals, except for salbutamol (59.7%), tiotropium bromide (20.0%) and beclometasone/formoterol (23.1%). Results of this survey suggested that the availability of drugs for COPD treatment in China is still an ongoing challenge for healthcare institutions. Insufficient drug supply and imbalanced drug availability among different hospitals are major barriers that warrant further improvements.